Pengembangan Kapasitas UMKM Kelompok Perajin Purun melalui Pelatihan Literasi Keuangan Digital - Jikrillah, Sufi; Firdaus, M. Riza; Widyarfhendi, Widyarfhendi; Ziyad, M. (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2025)
The issues faced by the "Purun Cantik" Handicraft Group MSMEs can be addressed through the utilization of digital technology, which is currently trending in Indonesia. Financial technology (Fintech) can assist MSMEs in financial areas such as funding, cashless transactions, payments, and more. The aim of this community service is to enhance the knowledge, understanding, and skills in digital finance for the members of the "Usaha Sejahtera Bersama" Purun Handicraft Group. If the Purun Cantik Handicraft Group possesses strong digital financial understanding and skills, it can improve their performance, business growth, and competitiveness. This mentoring activity begins with introductory materials on the digital transformation that MSME actors, especially those with a digital focus, must adopt. For digital-based MSME actors, the utilization of digital tools is essential to ensure continuous growth. The use of digital tools provides significant benefits for MSME actors in developing their businesses.